1996
DOI: 10.1007/s002800050420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of granisetron with doxorubicin or epirubicin on ECG intervals

Abstract: Commercially available serotonin-type 3 (5-HT3) receptor antagonists (ondansetron, granisetron, and tropisetron) have shown no clinically significant adverse effects on the cardiovascular system. In the dose-ranging evaluation of dolasetron, computer-generated ECGs revealed clinically asymptomatic prolongations of ECG intervals. We performed a clinical trial in which the possible changes in ECG intervals following a single 3-mg i.v. injection of granisetron and an injection of either doxorubicin or epirubicin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Jantunen et al designed a study focused specially on the cardiac effects of a 5-HT 3 receptor antagonist, granisetron (single 3 mg IV infusion) when used with cardiotoxic chemotherapy (doxorubicine or epirubicine) in 30 cancer patients. They observed only asymptomatic increases in the PR intervals, but no significant changes in QRS duration, cardiac rhythm, or QTc intervals [15]. Buyukavci et al [8] published their study which demonstrated the effects of ondansetron and granisetron on ECG in children receiving chemotherapy for acute leukemia.…”
Section: Discussionmentioning
confidence: 96%
“…Jantunen et al designed a study focused specially on the cardiac effects of a 5-HT 3 receptor antagonist, granisetron (single 3 mg IV infusion) when used with cardiotoxic chemotherapy (doxorubicine or epirubicine) in 30 cancer patients. They observed only asymptomatic increases in the PR intervals, but no significant changes in QRS duration, cardiac rhythm, or QTc intervals [15]. Buyukavci et al [8] published their study which demonstrated the effects of ondansetron and granisetron on ECG in children receiving chemotherapy for acute leukemia.…”
Section: Discussionmentioning
confidence: 96%
“…The cardiotoxicity of 5-HT 3 antagonists used as antiemetic on cancer-diagnosed patients receiving chemotherapy has been studied. Jantunen et al [20] studied the cardiac effect of 3 mg IV granisetron on 30 patients receiving cardiotoxic medication (doxorubicin, epirubicin). They did not detect any changes in ECG except for the prolongations in PR intervals before granisetron infusion and at the fifth and tenth minutes following the infusion.…”
Section: Discussionmentioning
confidence: 99%
“…The event was judged as unlikely to be related to the administration of granisetron, because cases of ventricular fibrillation have been reported in 944 patients who have received the agent in previous clinical studies of PONV, nor have any such cases been reported in the postmarketing surveillance of more than 20 000 granisetron-treated patients. Furthermore, the cardiac safety of granisetron has been demonstrated in studies involving both healthy volunteers and cancer patients [24,[26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%